Identification of Renal Parasite and its Blood Urea-Creatinine Profile on the Indonesian Indigenous Pigeons - Prastowo, J.; Sahara, A.; Marganingsih, C.; Ariyadi , B. (International Journal of Poultry Science, 2014)
In Indonesia, pigeon is one who is familiar with humans, beside can be consumed, usually maintained for hobby or pleasure. One of the parasitic worms that infect the pigeon's kidneys was Paratanaisia bragai (P. bragai). That worm can cause pathological changes in the renal pigeons. Evaluation of renal function can be done through checking of serum creatinine and urea. This study was conducted to identify the renal parasite and its blood urea-creatinine profile on the Indonesian indigenous pigeons. Fifty eight Indonesian indigenous pigeons were identified for renal parasite. Then all of the collected blood was evaluated for urea and creatinine levels. The difference values of urea and creatinine between infected and uninfected renal pigeon were analyzed by t-test. Fifty one percent (30/58) of them were infected by renal parasite. Identification of renal parasite showed the P. bragai. The creatinine levels in infected pigeons (2.650±1.7228) mg/dL were significantly higher than uninfected pigeons (1.732±1.2944) mg/dL. The blood urea levels showed non significant difference between the infected pigeons (7.7700±3.09775) mg/dL and the uninfected pigeons (6.4364±3.60415) mg/dL. The increase of urea and creatinine levels might be not correlated with the number of worms, since the Pearson correlation test showed no significant results. These results will be better if accompanied by histopathology of kidney, uric acid levels and other blood components.